2008
DOI: 10.1007/s12186-008-9011-4
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and Challenges on Learning and Construction of Identities at Work

Abstract: This paper analyses and discusses different constraints on workplace learning, vocational development and formation of identity. We ask how the learning and development of vocational identities are related to the various learning constraints and restrictions present in the socio-cultural contexts of the workplace. The study utilizes 20 interviews of industrial designers and nursing staff in Finland. The data on the vocational students was collected with Internet questionnaires (N= 1125) from these two fields; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Billett 2011;Felstead et al 2009a, b;Collin et al 2008). Hence, those in occupations accorded high social status have the opportunity to benefit (in identity terms) from the security and esteem accruing by virtue of their job.…”
Section: Implications For Occupational Identitymentioning
confidence: 99%
“…Billett 2011;Felstead et al 2009a, b;Collin et al 2008). Hence, those in occupations accorded high social status have the opportunity to benefit (in identity terms) from the security and esteem accruing by virtue of their job.…”
Section: Implications For Occupational Identitymentioning
confidence: 99%
“…Many of the constraints on the exercise of agency and on learning in hospital organizations have been found to be social (Collin et al, 2008;Ramanujam & Rousseau, 2006) and managerial (Carter, 2002;Mintzberg, 2012) in nature, rather than clinical or technical. Previous studies Lingard et al, 2004;Pisano et al, 2001) have indicated that the individual and technical nature of the work, status, and power hierarchies and unshared knowledge, deficient information flow, and the instability of the composition of teams are barriers to collaborative practice and learning across professional boundaries.…”
Section: Multiple Forms Of Professional Agency For (Non)crafting Of Wmentioning
confidence: 99%
“…Collin et al 2008;Hodkinson, Biesta and James 2008;Paloniemi and Collin 2010b), in order to understand work processes, the conditions and constraints within collaboration, and/or the development of expertise, processes at the individual and social levels must be seen as intertwined and, therefore, approached simultaneously and equivalently. This is a challenging task, conceptually and methodologically.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…Our focus on interprofessional collaboration derives from a socio-cultural understanding of learning (Wenger 1998). As many of the obstacles for learning in organisations (including health care organisations) have been found to be social in nature (Collin, Paloniemi, Virtanen and Eteläpelto 2008), we place a strong emphasis on the participatory nature of learning in work communities.…”
Section: Introductionmentioning
confidence: 99%